Inhibitory Effects of Sulfate and Nitrate Reduction on Reductive Dechlorination of PCP in a Flooded Paddy Soil - Xu, Yan; Xue, Lili; Ye, Qi; Franks, Ashley E.; Zhu, Min; Feng, Xi; Xu, Jianming; He, Yan (Frontiers in Microbiology, 2018)
Pentachlorophenol (PCP) is highly toxic and persistent in soils. Bioreduction of PCP often co-occurs with varying concentrations of sulfate and nitrate in flooded paddy soils where each can act as an electron acceptor. Anaerobic soil microcosms were constructed to evaluate the influence of sulfate and nitrate amendments and their redox processes. Microcosms with varying sulfate and nitrate concentrations demonstrated an inhibitory effect on reductive dechlorination of PCP compared to an untreated control. Compared to nitrate, sulfate exhibited a more significant impact on PCP dechlorination, as evidenced by a lower maximum reaction rate and a longer time to reach the maximum reaction rate. Dechlorination of PCP was initiated at the ortho- position, and then at the para- and meta- positions to form 3-CP as the final product in all microcosms. Deep sequencing of microbial communities in the microcosms revealed a strong variation in bacterial taxon among treatments. Specialized microbial groups, such as the genus of Desulfovibrio responding to the addition of sulfate, had a potential to mediate the competitive microbial dechlorination of PCP. Our results provide an insight into the competitive microbial-mediated reductive dechlorination of PCP in natural flooded soil or sediment environments.